Metagenomic insights into the distribution of antibiotic resistome between the gut-associated environments and the pristine environments. (May 2019) - Zeng, Jiaxiong; Pan, Yu; Yang, Jintao; Hou, Mengtian; Zeng, Zhenling; Xiong, Wenguang
Abstract: Antibiotic resistance genes (ARGs) in the environment are promoted by anthropogenic activities, which cause potential risks to human health. However, large-scale quantitative data on antibiotic resistome from the pristine and anthropogenic environments remains largely unexplored. Here, we used metagenome-wide analysis to investigate the share and divergence in ARG profiles and their potential bacterial hosts between the pristine and gut-associated environments. We found that the abundance of total ARGs in gut-associated environments was significantly higher than the pristine environments ( P < 0.001). The mcr-1 and tet X, the genes resistant to the last resort antibiotics (colistin and tigecycline, respectively), were in high abundance (4.57 copies/Gb and 3.39 copies/Gb, respectively) in gut-associated environments, suggesting the ARG pollution caused by anthropogenic antibiotics. Metagenomic assembly-based host-tracking analysis identified Escherichia, Bacteroides, and Clostridium as the predominant bacterial hosts of ARGs in gut-associated environments, while Alteromonas, Vibrio, and Proteobacteria as the predominant bacterial hosts of ARGs in pristine environments. We first described the broad diversity of ARG hosts in different environments using metagenome-wide analysis. Our results revealed the heterogeneous distribution of ARGs and their hosts among different microbial niches in gut-associated environments and the pristine environments. Highlights: Gut-associated microbiome had a higher detection rate of ARGs. Much larger concentration of intrinsical ARGs in pristine environments were found. ARGs exhibited a positive correlation with anthropogenic impacts. ARG hosts are not randomly distributed in heterogeneous environments.